Matemática na produção agrícola: no uso da função quadrática e do polinômio de Lagrange aplicado no ensino médio - Silva, Antônio de Souza (Brasil, 2023)
Agricultural production plays an important role in life in society and this importance is evident in the school life of our students, who actually use this information to work on content in the classroom. In addition to knowing the agricultural production of rice, beans, corn and cassava in the city of Bacabal, students will work on the concept of a quadratic function, calculating the maximum and minimum point of production in tons and being able to represent these points in GeoGebra, in a way individual, calculating the initial function of each given information, showing in the software. In addition to representing the maximum and minimum points, the students will calculate the function that represents the information given by the bars in the graph, using the Lagrange polynomial method, where the maximum and minimum points will be shown on a scale that shows all the values of the worked graph.